2022
DOI: 10.3389/fcvm.2022.872115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prognostic Guided Management of Patients With Acute Pulmonary Embolism According to the European Society of Cardiology Risk Stratification Model

Abstract: BackgroundA recent trial showed that management driven by prognostic assessment was effective in reducing the length of stay (LOS) for acute stable pulmonary embolism (PE). The efficacy and safety of this strategy in each subgroup of risk stratification remains unknown.MethodsWe conducted a post-hoc analysis of the randomized IPEP study to evaluate the effect of a management strategy guided by early use of a prognostic pathway in the low- and intermediate-high risk subgroups defined by the European Society of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Our study also found that the clinic severity of acute HR-SPE was more severe than that of NHR-SPE. Severe PE often requires a longer LOS to complete the treatments 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that the clinic severity of acute HR-SPE was more severe than that of NHR-SPE. Severe PE often requires a longer LOS to complete the treatments 36 , 37 .…”
Section: Discussionmentioning
confidence: 99%